National production planning model for the Philippine sugar industry - Jalbuena, Isagani J.
The main purpose of the study is to develop an aggregate production planning model for the sugar industry in the Philippines to help alleviate the industry's present situation. The principal thrust of the examination will be centered on the agricultural and industrial sectors of the industry to help identify the components, variables, parameters, and relationships that makes up the sugar production system of the country. These factors will aid in the development and design of the aggregate production planning model. At the national level, the industry's performance was taken as a whole. That is, sugar centrals from a given region were placed together under one group as one sample. The components and variables were identified and their relationships were ascertained. The production management tools such as forecasting techniques, mathematical programming, and simulation were used to determine an aggregate production planning model for the entire industry. The aggregate production plan took into account the domestic demand of raw sugar, the country's export share as provided by the International Sugar Agreement of 1977, the milling capabilities and storage capacities of each mill districts, the farm and factory yields, sugar prices and total production cost in calculating how much to produce. At the regional level, the study attempted to identify the factors that could be considered as components and variables of the industry. Having identified the variables and components, the next step was to determine the relationships of one variable to the other, one component to another, one variable to a component, and so on. Simulated sampling, known as the Monte Carlo technique tested the performance of the two identified, distinct milling procedures in the sugar industry of the country. Samples from different mill districts of the three regions of the study namely, Negros, Panay, and Luzon were tested to comparatively show the difference in performance, efficiency, and profitability of each process or procedure. Each region showed different outcomes due to contrasting farm and factory yields. The study however, does not intend to completely include all the multifaceted aspects of the sugar industry. The marketing and trading sector of the sugar industry will not be included. A description, analysis, and evaluation of this sector alone would take volumes of work.